Electrokinetics and Electrohydrodynamics in Microsystems - Ramos, Antonio (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2011)
Among the most promising techniques to handle small objects at the micrometer scale are those that employ electrical forces, which have the advantages of voltage-based control and dominance over other forces. The book provides a state-of-the-art knowledge on both theoretical and applied aspects of the electrical manipulation of colloidal particles and fluids in microsystems and covers the folllowing topics: dielectrophoresis, electrowetting, electrohydrodynamics in microsystems, and electrokinetics of fluids and particles. The book is addressed to doctoral students, young or senior researchers, chemical engineers and/or biotechnologists with an interest in microfluidics, alb-on-chip or MEMS.